EXPERIMENTAL STUDY TO EVALUATE THE HYDRAULIC PERFORMANCE OF BASTORA DAM STEPPED SPILLWAY - HUSAIN, SARHANG M.; AHMED, SHAHIN S. (Journal of Duhok University, 2017)
This study aims to evaluate the performance of proposed design for Bastora dam stepped spillway project. Experiments are conducted on a physical model, which is constructed at the laboratory of hydraulic engineering/ college of engineering/ Salahaddin University, Erbil- Iraq using an appropriate scale to avoid potential effects governing the model. The evaluation includes determining the flow regime passing the structure, length to and flow depth at the inception point, the efficiency of the structure to dissipate the energy at the toe, the height of side wall required for both the spillway chute and stilling basin at the downstream of the spillway and discharge coefficient. The results presented in the design report are compared with those measured/determined in this study and the design formulae of stepped spillway available in the literature. Although the comparisons show few discrepancies between the results, especially in terms of the energy dissipation rate and chute side wall dimension, the design report can be said acceptable and reliable.